2023
DOI: 10.1186/s40643-023-00695-8
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of multi-enzyme complexes based on the design of scaffold protein

Xiangyi Wang,
Yi Jiang,
Hongling Liu
et al.

Abstract: Multi-enzyme complexes designed based on scaffold proteins are a current topic in molecular enzyme engineering. They have been gradually applied to increase the production of enzyme cascades, thereby achieving effective biosynthetic pathways. This paper reviews the recent progress in the design strategy and application of multi-enzyme complexes. First, the metabolic channels in the multi-enzyme complex have been introduced, and the construction strategies of the multi-enzyme complex emerging in recent years ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 155 publications
0
1
0
Order By: Relevance
“…Protein-protein interactions play a crucial role in cellular processes, and understanding these interactions is fundamental for elucidating biological mechanisms (Wang et al 2023 ). Previous studies have shown that PlaS enhances the expression of PlaA1 and promotes its enzymatic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Protein-protein interactions play a crucial role in cellular processes, and understanding these interactions is fundamental for elucidating biological mechanisms (Wang et al 2023 ). Previous studies have shown that PlaS enhances the expression of PlaA1 and promotes its enzymatic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes are proteins or RNAs produced by living cells with high specificity and catalytic efficiency, and are catalysts for all intracellular chemical reactions. Since enzymes are widely distributed in plants, bacteria, and insects, they are secreted in large quantities, especially in plant pests and diseases, including amylase, pectinase, glucosidase, cellulase, and laccase. These enzymes can destroy structures on the plant surface, which allows for the invasion of pests and diseases because the fact that the process of plant infestation by pests and diseases is a complex class of enzyme-chemical processes. , Enzyme stimulation-responsive controlled release systems tend to be highly specialized, specific, targeted, efficient, and biocompatible under mild reaction conditions. , Based on this, enzyme-stimulated response controlled release is one of the most promising stimulation methods.…”
Section: Stimulus-responsive Controlled Releasementioning
confidence: 99%